Enhancing Employee Satisfaction through Cultural, Motivational, and Environmental Drivers: A Case Study of PLN ULP Singaraja - Dirgayusa, I Bagus Raka; Widiastini, Ni Made Ary; Rahmawati, Putu Indah (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of work culture, work motivation, and work environment on employee job satisfaction at PT PLN (Persero) Customer Service Unit (ULP) Singaraja. The phenomenon underlying this research is the mismatch between the company’s promoted work culture values and actual practices in the field, the decline in employee motivation due to heavy workloads, and the suboptimal physical work environment conditions. This research employs a quantitative approach with a survey method. The study population consists of all 121 employees of PLN ULP Singaraja, with a total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 21. The results show that work culture and work motivation have a positive and significant effect on job satisfaction, while the work environment has a positive but insignificant effect. Simultaneously, the three variables significantly affect job satisfaction, with work motivation being the most dominant factor. These findings emphasize that improving employee job satisfaction is more effectively achieved through strengthening individual motivation and internalizing work culture values, accompanied by maintaining the existing work environment. This study is expected to serve as a strategic reference for management in designing policies to enhance employee well-being and productivity.